2022
DOI: 10.1002/jez.b.23117
|View full text |Cite
|
Sign up to set email alerts
|

Expression of spidroin proteins in the silk glands of golden orb‐weaver spiders

Abstract: The expression of spidroins in the major ampullate, minor ampullate, flagelliform, and tubuliform silk glands of Trichonephila clavipes spiders was analyzed using proteomics analysis techniques. Spidroin peptides were identified and assigned to different gene products based on sequence concurrence when compared with the whole genome of the spider. It was found that only a relatively low proportion of the spidroin genes are expressed as proteins in any of the studied glands. In addition, the expression of spidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Our gene expression profiling demonstrated examples of gland-specific expression of spidroin genes, as well as spidroins broadly expressed across multiple glands. On this particular point, we note very recent work which reached similar conclusions from analysis of protein expression of silk glands in orb-weaving spiders as well [ 46 ], further supporting that diverse spidroin expression is functionally consequential. Finally, characterization of expression in males elucidated the catalog of spidroins utilized by males, and the complement of spidroins utilized by females, including multiple MaSp and Flag transcripts.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our gene expression profiling demonstrated examples of gland-specific expression of spidroin genes, as well as spidroins broadly expressed across multiple glands. On this particular point, we note very recent work which reached similar conclusions from analysis of protein expression of silk glands in orb-weaving spiders as well [ 46 ], further supporting that diverse spidroin expression is functionally consequential. Finally, characterization of expression in males elucidated the catalog of spidroins utilized by males, and the complement of spidroins utilized by females, including multiple MaSp and Flag transcripts.…”
Section: Discussionsupporting
confidence: 80%
“…Previous work has demonstrated that spidroins assigned to a particular gene class are not exclusively transcribed in the silk gland in which the gene is assigned [ 8 , 13 ] with proteomic analyses also indicating diverse protein expression across silk glands [ 46 ]. To validate and compare transcription levels across silk glands, we directly interrogated the degree of spidroin expression bias by using quantitative PCR (qPCR) to measure RNA transcript levels in morphologically classified silk gland isolates and control tissues isolated from three field-collected adult females ( Methods, Quantitative PCR (qPCR) analysis ).…”
Section: Resultsmentioning
confidence: 99%
“…MaSp silk fibers are used in a range of roles such as the dragline, the web frame, the web radii and ballooning, but compositional differences among these utilities has not been investigated. These spidroins may also be incorporated, to some extent, into non-canonical roles (e.g., prey wrapping), and gene expression analyses from this study (Fig 6) and others [81,98] indicate MaSp expression is not limited to the major ampullate gland. Overall, selection is likely to favor the use of different MaSp types for different functional roles as well as the flexibility to alter silk fiber composition depending on specific ecological conditions.…”
Section: Masp Gene Diversity Is Shaped By Complex Evolutionary Mechan...mentioning
confidence: 61%
“…Such architectural qualities would be subject not only to the molecular properties of the spidroins forming the fibers, but also to the physical constraints of spider silk-spinning systems Vollrath 2001, 2002;Chen et al 2006). These are, however, significant endeavors requiring combined genomic and proteomic analyses, the first of which (in the spider Trichonephila clavipes) has just recently been published (Jorge et al 2022). The present study, however, offers a primer on identifying the relevant molecular differences between spidroins that substantiate their wide range of mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in spidroin sequences of two spiders with different α* values are likely playing a role in the distinctive overall mechanical properties of these silks, such as the breaking of hydrogen bonds associated with the "entropic unfolding" deformation phase dragline fibers experience at intermediate strains (Yarger et al 2018). It must be highlighted that the full relevance of this analysis can only be obtained after characterizing not only the differences between distinct protein sequences, but also determining their quantitative presence in the MA fibers of each species (Jorge et al 2022). However, even without this information, it is possible to establish some key differences in the structures of A. aurantia and L. hesperus MaSps that offer clues on the origin of the different tensile properties of both materials.…”
Section: Implications Of Masp Molecular Structure For α* Parameter Va...mentioning
confidence: 99%